2020
DOI: 10.1002/chem.202000836
|View full text |Cite
|
Sign up to set email alerts
|

A Silylene–Germylene Molecule Containing a SiI−GeI Single Bond

Abstract: Scheme1.Structures of nonclassical triple bond and bis-metallylene.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…In 2020, Sun, Li, Wang and co-workers presented new lithium germylidenide and silylene-germylene complex (Scheme 3-20). 130 The reduction of β-diketiminato germanium(II) chlorides 3-20-1 with Li gave the corresponding germylidenide complex 5CNGe5 and 5CNGe6, respectively. XRD analysis revealed that the almost planar C3NGe ring with the interior angle summation (Σ int) of 539.8° (5CNGe5) and 550.0° (5CNGe6).…”
Section: Gementioning
confidence: 99%
“…In 2020, Sun, Li, Wang and co-workers presented new lithium germylidenide and silylene-germylene complex (Scheme 3-20). 130 The reduction of β-diketiminato germanium(II) chlorides 3-20-1 with Li gave the corresponding germylidenide complex 5CNGe5 and 5CNGe6, respectively. XRD analysis revealed that the almost planar C3NGe ring with the interior angle summation (Σ int) of 539.8° (5CNGe5) and 550.0° (5CNGe6).…”
Section: Gementioning
confidence: 99%
“…The first isolated example, compound 13 , prepared by salt metathesis of a germylene anion and a chlorosilylene, was only reported in 2020 by Wang and co‐workers (Figure 6). [27] A similar base‐stabilized silylene‐germylene 14 was observed as a transient species that decomposes in solution even at −30 °C [28] . Consequently, compound 12 is only the second isolated, fully characterized example of this interesting class of low‐valent compounds.…”
Section: Resultsmentioning
confidence: 94%
“…It is because the reactive Ë‐Ë' moiety makes such complexes difficult to isolate. Thus far, only a handful of examples were reported, where the sterically hindered germylidenide anions [:G̈e{C(R 1 )C(R 2 )C(R 1 )N(Ar)}] – (R 1 = Me/Ph, R 2 = H/Ph) reacted with the β‐diketiminato chlorostannylene and amidinato chlorosilylene to form the corresponding base‐stabilized germylenylstannylene and –silylene . Interestingly, their reactivity was never reported.…”
Section: Introductionmentioning
confidence: 99%